Penerapan Aplikasi Manajemen Laboratorium Dinas Lingkungan Hidup Kota Palembang - Dedi Irawan; Rezky Nugraha Salim (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Waste samples that is managed properly will generate added value and provide benefits for environmental management. The purpose of this study is to design a web-based waste water sample data management information system so that it can make it easier for waste laboratory staff and the public as customers and admins to manage and access waste water sample data and transactions. The method used in data collection is the DevOps method and it is also not important as a researcher to interview officials from the Palembang city environmental service regarding the laboratory management application program.. In making the website, the author uses the PHP and MySQL programming languages with the DevOps development method, object-based software modeling using UML and designing the system interface to show system functions. Database design is made to show the relationship between entities and data contained in the system. Users who will use the waste laboratory management application information system are employees of the environmental service laboratory unit as admin and the public. The results of this study indicate that the website design that was built can make it easier for the admin to manage waste water sample data, it can be stored in a database and can be accessed at any time. Apart from that, for residents,, this system has the benefit of accelerating the process of collecting waste in their environment, this system has the benefit of speeding up the process of collecting waste water sample data.